Investigating Human‐Induced Changes of Elemental Cycles in the Great Lakes: Recent Changes in the Biogeochemistry of the Great Lakes System; Detroit, Michigan, 11–13 March 2013. (9th July 2013) - Baskaran, Mark; Bratton, John
Abstract : Food webs and associated elemental cycles in the Laurentian Great Lakes have been considerably altered over the past 30 years due to factors such as phosphorus abatement, introduction of zebra and quagga mussels, and climate change. These perturbations provide a unique opportunity to document how this natural system has responded and possibly to predict future changes in biogeochemical cycling.